2016
DOI: 10.1108/arj-05-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Cheating behaviour among accounting students: some Malaysian evidence

Abstract: Purpose This study aims to examine the cheating behaviour among accounting students in terms of the extent of neutralization of cheating and the effectiveness of deterrents to cheating of cheaters and non-cheaters. It also aims to examine the differences in the cheating behaviour between males and females of cheaters and non-cheaters groups. Design/methodology/approach Using a questionnaire survey on academic dishonesty developed by Haines et al. (1986) which was administered to accounting students, 435 usab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
(52 reference statements)
2
23
2
3
Order By: Relevance
“…Hence, female students are less likely to engage in academic dishonesty than male students. This finding is consistent with a study conducted among accounting students in Malaysia that revealed that male students were less likely to follow rules than female students 35 …”
Section: Discussionsupporting
confidence: 92%
“…Hence, female students are less likely to engage in academic dishonesty than male students. This finding is consistent with a study conducted among accounting students in Malaysia that revealed that male students were less likely to follow rules than female students 35 …”
Section: Discussionsupporting
confidence: 92%
“…Both have been studied by several researchers and found significant relationship with a person's behavioural action. Ismail and Yussof (2016) found that gender factor has a significant impact in cheating behaviour. Haswell et al (1999) argue that gender has strong influence in student's ethical perception.…”
Section: Literature Review and Hypothesis Develpomentmentioning
confidence: 97%
“…Seorang akuntan perlu mematuhi prinsip dasar etika agar dapat menjadi Akuntan Profesional yang merupakan penerus informasi. Tidak etis apabila mahasiswa yang akan berperan penting pada keuangan perusahaan sudah terbiasa melakukan perilaku kecurangan akademik sejak masa perkuliahan mereka, sehingga dapat menyebabkan skandal perusahaan di masa depan (Ismail & Yussof, 2016). Prinsip dasar seorang akuntan terlampir pada Kode Etik Akuntan Profesional oleh Ikatan Akuntansi Indonesia (poin 100.5), yang menyatakan seorang akuntan harus memiliki integritas, objektivitas, kompetensi dan kehati-hatian profesional, kerahasiaan, dan perilaku profesional.…”
Section: Pendahuluanunclassified
“…Terakhir penelitian oleh Ismail & Yussof (2016) di Malaysia. Hasil penelitian ini memperlihatkan bahwa, laki-laki memiliki kecenderungan yang lebih besar untuk melakukan kecurangan dalam ujian serta untuk membenarkan kecurangan daripada wanita, hal ini konsisten dengan teori diferensiasi sosial.…”
Section: Pendahuluanunclassified